The Relationship between Learning Styles (Convergent and Divergent) and the Effect of Random and Blocked Practices on the Learning of Badminton Serve Skills - Mohammad Taghi Aghdasi; Sima Abdolzadeh (University of Tehran, 2015)
The present study aimed at determining the relationship between learning styles and the effect of random and blocked practices on learning of badminton serve skills.  In this quasi-experimental study, 48 female high school students were randomly placed in four groups: 1. convergent learning style with random practice, 2. convergent learning style with blocked practice, 3. divergent learning style with random practice and 4. divergent learning style with blocked practice. After the pretest, subjects went through the acquisition phase under specific conditions of each group and then participated in retention and transfer tests. Kolb Learning Styles Questionnaire (KLSI) and French short serve test and Scott and Fox high serve tests were used. ANOVA was used to compare the scores of the four groups. Findings showed differences among immediate retention, delayed retention and learning transfer (P<0.05). Convergent learning style and random practice were more effective than divergent learning style and blocked practice to learn badminton serve skill (P<0.01). Therefore, focusing on the role of learning styles and learning intervention in instructing serve skills gains importance.